AquaNet - 16S Bacteria Reads from Feresjön AquaNet platform, 2017-06-05–2017-09-11 - Asa Research Station (Swedish University of Agricultural Sciences, 2019)
Mesocosm experiment focusing on fish pulse and light reduction as treatment effects ran simultaneously at the SITES stations Asa, Erken, Skogaryd, Svartberget and Bolmen during summer 2017. Data contains number of reads per Operational Taxonomic Unit of 16S Bacteria.
Asa Research Station (2019). AquaNet - 16S Bacteria Reads from Feresjön AquaNet platform, 2017-06-05–2017-09-11 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/it-hvhfnLE4puXyLWd7ChE5t
Keywords: SITES AquaNet; Bacteria/Archaea; Community Structure; Ecosystem functions; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap